LAW PROTECTION TOWARDS TRADEMARK OF PT. VIONA DUTA SAMUDRA THROUGH TRADEMARK REGISTRATION ACCOMPANIMENT - Vizta Dana Iswara; Tantimin Tantimin (Universitas Internasional Batam, 2022)
Indonesian people have realized how important it is to register a trademark for their business. Because, the brand is an identity of a business which means the brand serves as a differentiator for a product or service which is intended to show the characteristics and origin of a product or service. Therefore, it is necessary to register the Mark with the Directorate General of Intellectual Property in order to obtain rights to the Mark. Meanwhile, the registration process for Marks can be found in Law no. 20 of 2016 concerning Brands and Geographical Indications. With the regulation on this mark, a registered mark can have legal protection from the state. The protection referred to in this context is in the form of legal protection where the registered mark cannot be used by other parties without being known and without the permission of the Mark owner. Thus, by having a certificate of right to a mark, directly the party who registered the mark or in other words the applicant for the registration of the mark has become the legal owner of the mark for the goods and/or services. In addition to functioning as property rights, trademark certificates can also serve as proof of legal ownership of goods and/or services when in court. PT. Viona Duta Samudra is a company engaged in the service sector where the main focus of its business is the processing of legal documents for Foreign Workers (TKA) but it is known that PT. Viona Duta Samudra has not registered its trademark with the Directorate General of Intellectual Property (DJKI). So, the author tries to help the company to register the trademark so that the company can avoid disputes and actions by persons who do not have good faith related to the owner's mark. The research method implemented by the author in this study is an empirical legal research methodology, where the author uses primary data in the form of face-to-face interviews and observations supported by secondary data in the form of library research. Meanwhile, the receipt of the application for trademark registration is the result of the trademark registration process of PT. Viona Duta Samudra.